(untitled) (Revista Brasileira Multidisciplinar, 2026)
Introduction: : Stroke is characterized by focal neurological deficits of sudden onset and vascular etiology. Transient Ischemic Attack (TIA) corresponds to a temporary interruption of cerebral blood flow, with transient symptoms, no permanent sequelae, and represents a risk factor for future strokes. Objective: To analyze the epidemiological profile of hospitalizations and hospital deaths due to transient ischemic stroke and related syndromes in Brazil. Methodology: Observational, descriptive, time-series epidemiological study, based on secondary data from SIH/SUS-DATASUS, collected in 2025. Hospitalizations and deaths due to transient ischemic stroke and related syndromes were analyzed in Brazil between 2019 and 2024, according to region, sex, race/color, and year, using Excel 2019 for descriptive analysis. Results: Between 2019 and 2024, 122,189 hospitalizations and 10,697 deaths due to transient ischemic stroke and related syndromes were recorded in Brazil. A predominance of males was observed, with a concentration of cases and deaths in the Southeast region. Individuals aged 60 years or older accounted for 71.4% of hospitalizations. The findings highlight an epidemiological burden, regional inequalities, and the need to strengthen prevention strategies, early diagnosis, and specialized care. Conclusion: TIA and related syndromes represent a significant public health concern in Brazil, with a greater impact among older adults and a higher concentration of cases in the Southeast and South regions. The findings highlight the need to strengthen prevention strategies, early diagnosis, timely management, and continuous follow-up, while reducing regional disparities in access to healthcare services in order to decrease the morbidity and mortality associated with cerebrovascular diseases.